If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -1(13 + 4x) = -3(5 + -9k) + 2 -1x + (13 * -1 + 4x * -1) = -3(5 + -9k) + 2 -1x + (-13 + -4x) = -3(5 + -9k) + 2 Reorder the terms: -13 + -1x + -4x = -3(5 + -9k) + 2 Combine like terms: -1x + -4x = -5x -13 + -5x = -3(5 + -9k) + 2 -13 + -5x = (5 * -3 + -9k * -3) + 2 -13 + -5x = (-15 + 27k) + 2 Reorder the terms: -13 + -5x = -15 + 2 + 27k Combine like terms: -15 + 2 = -13 -13 + -5x = -13 + 27k Add '13' to each side of the equation. -13 + 13 + -5x = -13 + 13 + 27k Combine like terms: -13 + 13 = 0 0 + -5x = -13 + 13 + 27k -5x = -13 + 13 + 27k Combine like terms: -13 + 13 = 0 -5x = 0 + 27k -5x = 27k Solving -5x = 27k Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-5'. x = -5.4k Simplifying x = -5.4k
| -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) | | 3y-7=2y+5 | | 3-6x=-80-5x | | 4+-1x=1x+4 | | x^2+1x=272 | | -2y+8=3y+28 | | 6x^24= | | 3x+1.5x+x+180=455 | | 6(4x-3)-10= | | 7x+9x-69=46-7x | | 2(9x-1)=99-7(3-4k) | | 8n-3.5=-20 | | z/2+1=7z/2 | | 10(1+30b)=-20 | | 2x+8-k=-3 | | 24-4= | | 20z+80=140+10x | | -(3x-2)-(x+4)=-(2x-2)-(2x+4) | | 10+30b=-2 | | 11520=32x^2+64x | | 9x-4x-15=-35 | | 2(6x)+2(8x-10)= | | -17=-1x+2x-7 | | 4-3x=-2x | | 0.5b+4=29(b+2) |